Perfil socioeconômico de produtores que aderiram ao PROSAF no município de Mojuí dos Campos - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Agroforestry systems are an important tool in combating rural poverty, food security and conservation of natural resources. To meet the demands for SAFs in all regions of the state of Pará, the Institute for Forestry and Biodiversity Development created the PROSAF project, with the objective of recovering anthropically altered areas in small rural family properties, in addition to assisting in the socioeconomic development, security food and environmental preservation in communities with altered areas. The present work aimed to outline the socioeconomic profile of farmers registered in the PROSAF project, in the municipality of Mojui dos Campos, in the year 2021. To determine the socioeconomic profile of farmers, a systematization of the information obtained by observing the responses of producers à 13 questions selected from more than 50 contained in the register applied to farmers upon registration. Data were quantitatively evaluated using the descriptive statistics method, and qualitative data using the frequency distribution method. The results showed relevant data, the vast majority of rural producers who joined the program are male farmers, who are also the most authoritative figure in the family hierarchy, with an average age of 45 years, married, with a low level of education. As for the source of income, it predominantly comes from subsistence agriculture, with emphasis on the cultivation and commercialization of cassava and its derivatives, in relation to the condition of the farmer in relation to the land, the vast majority do not have any documentation regarding their ownership, they do not receive technical assistance. regularly.
Keywords: SAFs; Projeto PROSAF; Perfil socioeconômico; Agricultura familiar; CNPQ:: ENGENHARIAS